Collaborative innovation relationship in Yangtze River Delta of China: Subjects collaboration and spatial correlation. (May 2022) - Tao, Zhuang; Shuliang, Zhao
Abstract: In the regional innovation system (RIS), the triple helix (TH) relations of university, industry, government (UIG) have received wide attention, but the spatial correlation involving various innovation subjects has rarely been deeply analyzed, especially in urban agglomeration. Based on the triple helix perspective, this paper integrates the collaborative coupling relationship between innovation subjects and the spatial correlation between regions in the RIS under a theoretical framework. Two types of collaborative innovation networks are constructed: one is the collaborative coupling network between UIG, one is the spatial correlation network between different areas. Using the invention patent data of provinces in the Yangtze River Delta (YRD) from 2014 to 2018, and on account of the TH algorithm based on mutual information, to explore the collaborative innovation relationship from the two dimensions of collaborative coupling among innovation subjects and spatial correlation among regions. The results show that:(1) Jiangsu has an obvious leading advantage in the total amount of invention patents, Zhejiang and Anhui have witnessed a rapid growth of patent output. (2) In the YRD region, the collaboration between university and industry is the closest, the UIG collaborative relationship is close in Shanghai, the collaborative relationship between industry and university in Jiangsu is close. (3) The bilateral correlation between Jiangsu and the other three provinces is relatively strong; the bilateral correlation between Zhejiang and the other three provinces tends to be close. The trilateral correlation among Jiangsu, Zhejiang, and Anhui is relatively close. This study expands the application fields of the TH theory and provides a new perspective and method for RIS research. The research results offer helpful theoretical support and policy inspiration for accurately grasping the development law of the regional innovation in the YRD and coordinating the relationship between different subjects and different regions in the innovation network. Highlights: Integrates subjects collaboration and spatial correlation in the regional innovation system into a theoretical framework. The theoretical model of regional collaborative innovation is proposed and its mechanism is expounded. The collaborative coupling between UIG, and the spatial correlation between different areas are investigated. Using the invention patent data of provinces, empirically examines the collaborative innovation relationship in the YRD.